International Joint Conference SOCO'16-CISIS'16-ICEUTE'16 : San Sebastián, Spain, October 19th-21st, 2016 Proceedings /: San Sebastián, Spain, October 19th-21st, 2016 Proceedings. ([2016]) - Unknown
No abstract available